Outcome of patients with double valve surgery between 2009 and 2018 at University Hospital Basel, Switzerland - Egger, Martin L.; Gahl, Brigitta; Koechlin, Luca; Schömig, Lena; Matt, Peter; Reuthebuch, Oliver; Eckstein, Friedrich S.; Grapow, Martin T. R. (Journal of cardiothoracic surgery, 2022)
Background In isolated mitral valve regurgitation general consensus on surgery is to favor repair over replacement excluding rheumatic etiology or endocarditis. If concomitant aortic valve replacement is performed however, clinical evidence is more ambiguous and no explicit guidelines exist on the choice of mitral valve treatment. Both, double valve replacement (DVR) and aortic valve replacement in combination with concomitant mitral valve repair (AVR + MVP) have been proven to be feasible procedures. In our single-center, retrospective, observational cohort study, we compared the outcome of these two surgical techniques focusing on mortality and morbidity. Methods 89 patients underwent DVR (n = 41) or AVR + MVP (n = 48) in our institution between 2009 and 2018. Follow-up data was collected using electronic patient records, by contacting treating physicians and by telephone interviews. We used the Kaplan–Meier method to analyze mortality during follow-up and Cox regression to investigate potential predictors of mortality. Results During a median follow-up duration of 4.5 [IQR 2.9 to 6.1] years, there was no significant difference in mortality between both cohorts. Thirty days mortality was 6.3% in the DVR and 7% in the AVR + MVP cohort. Overall mortality amounted to 17% for DVR and 23% for AVR + MVP. DVR was the preferred procedure for valve disease of rheumatic etiology and for endocarditis, while in degenerative valves AVR + MVP was predominant. More biological valves were used in the AVR + MVP cohort ( p < 0.001) and more mechanical valves were implanted in the DVR cohort. The rate of rehospitalization, deterioration of left ventricular ejection fraction and postoperative complications were equally distributed among the two cohorts. Conclusion Our data analysis showed that both DVR and AVR + MVP are safe and feasible options for double valve surgery. Based on our findings we could not prove superiority of one surgical technique over the other. Choosing the appropriate procedure for the patient should be influenced by valve etiology, patients’ comorbidities and the surgeons’ experience. Trial registration This was a retrospectively registered trial, registered on April 1st 2018, ClinicalTrials.gov Identifier: NCT03667274.